Otimização da captação de energia solar por meio da automação dos painéis solares - Carmo, João Mateus Dias do (2020)
The capture of solar energy has several approaches, which have undergone changes over the years with the emergence of new technologies and concepts. The capture via solar panels is a well known method because it is a technology on the rise nowadays, both because of the ease of implantation, because the installation and configuration of the solar panels are simple, and because of their environmental characteristics, as the damage to nature is negligible in relation to other forms of energy generations, being considered a clean energy, different from technologies that use the burning of fossil and hydroelectric fuels. In this work, the theoretical basis on the movement of solar panels will be addressed, with the objective of achieving greater energy efficiency of the system, being compared with scenarios having fixed panels, showing that the energy gain is higher than the cost of moving the solar panels. With the main contribution of this work, the development of a system capable of making solar capitation from the movement of actuators, in order to optimize the angle of inclination of the solar panel with the angle of incidence of the sun’s rays. Finally, an analysis will be carried out based on the results obtained from the implementation, showing a promising strategy for moving solar panels. In addition to suggestions for integrating the system with concepts such as internet of things.